Democracy in Islam: comparative study of Muhammad Abid al-Jabiri and Abdolkarim Soroushâs thoughts - Susanto, Happy (Indonesian Journal of Islam and Muslim Societies, 2011)
Using analytic and interpretative approaches, this research compares al-Jabiriand Soroushâs thoughts about democracy in Islam. To assess Islamâs compatibilitywith democracy, this thesis will analyze the issues of authority, sharia, andfreedom according to the two scholars. Al-Jabiri and Soroush agree that theconcept of authority in Islam cannot be interpreted simply as Godâs sovereignty,but it also concerns human rights and sovereignty. A leader put justice as his/hercentral concern in practicing policies for citizens. To pursue this hope, they alsopropose that sharia should be reinterpreted in order to be harmonizing in accordancechanging circumstances and time. Al-Jabiri has different understandingwith Soroush about the relationship between religion and state. Al-Jabiri seesthat Muslims are free to choose democracy as their political life. He doesnâtagree the integration of religion and state. In this case, he doesnât agree theimplementation of sharia in the state. Meanwhile Soroush sees that religion hasan important role in the state, so that he agrees the implementation of shariabecause according to him it supports the political process of the state.Muhammad Abid al-Jabiri dan Abdolkarim Soroush merupakan intelektual Muslimyang memandang bahwa Islam kompatibel dengan demokrasi, dan keduanyatermasuk dalam kelompok moderat. Untuk menguji apakah Islam kompatibeldengan demokrasi, artikel ini menganalisis isu-isu otoritas, syariah, dan kebebasanmenurut pandangan kedua tokoh tersebut. Kedua intelektual itu memilikipandangan filosofis yang sejalan tentang ide demokrasi dalam Islam. Misalnya,konsep otoritas dalam Islam tidak saja dipahami sebagai bentuk kedaulatan Tuhan,namun yang lebih penting bahwa konsep ini juga memerhatikan aspek hak dankedaulatan manusia. Syariah perlu direinterpretasi agar sesuai dengan konteksperubahan zaman dan dapat mengarah pada pencapaian tujuannya. Perbedaankeduanya terletak pada relasi agama-negara. Dalam hal ini, al-Jabiri memilikipandangan yang âliberalâ bahwa konsep sebuah negara tidak perlu berdasarkanidentitas agama. Umat Islam diberikan kebebasan penuh untuk menjalankankehidupan politiknya, tanpa terbebani oleh rujukan teks-teks Islam yang masihdiperdebatkan. Dengan demikian, ia memandang bahwa penerapan syariah dalamsebuah negara tidak perlu karena sesungguhnya syariah belum penah diterapkansecara sempurna. Sedangkan Soroush berpandangan sebaliknya bahwa identitasagama perlu ditambatkan ke dalam ide sebuah negara (demokrasi).